Cholinesterase based amperometric biosensors for assay of anticholinergic compounds - Pohanka, Miroslav (Interdisciplinary toxicology, 2009)
Biosensors are analytical devices being approachable for multiple analytes assay. Here, biosensors with intercepted acetylcholinesterase (AChE) or butyrylcholinesterase (BChE) are presented as tool for assay of anticholinergic compounds such as pesticides, nerve agents and some natural toxins. Principle of assay is based on evaluation of cholinesterase activity and its pertinent decrease in presence of analyte. Nerve agents, pesticides, anticholinergic drugs useable for treatment of Alzheimer's disease as well as myasthenia gravis and aflatoxins are enlisted as compounds simply analyzable by cholinesterase biosensors.
Keywords: biosensor; amperometry; carbamates; acetylcholinesterase; butyrylcholinesterase; organophosphonates; organophophates